2019
DOI: 10.3390/ijms20061425
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Multiple Organellar RNA Editing Factor Family in Poplar Reveals Evolution and Roles in Drought Stress

Abstract: Poplar (Populus) is one of the most important woody plants worldwide. Drought, a primary abiotic stress, seriously affects poplar growth and development. Multiple organellar RNA editing factor (MORF) genes—pivotal factors in the RNA editosome in Arabidopsis thaliana—are indispensable for the regulation of various physiological processes, including organelle C-to-U RNA editing and plasmid development, as well as in the response to stresses. Although the poplar genome sequence has been released, little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…In A. thaliana , MORF proteins can form homodimers and heterodimers that participate in RNA editing [5,14]. Although the MORF genes were reported to respond to abiotic stress in poplar, few reports have been published on the functions of OsMORFs and their responses to abiotic stress in rice [3]. In this study, we provide further insight into the structure of the OsMORF genes family, its tissue expression patterns, and responses to cold and salt stresses, as well as the interactions between OsMORF proteins.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In A. thaliana , MORF proteins can form homodimers and heterodimers that participate in RNA editing [5,14]. Although the MORF genes were reported to respond to abiotic stress in poplar, few reports have been published on the functions of OsMORFs and their responses to abiotic stress in rice [3]. In this study, we provide further insight into the structure of the OsMORF genes family, its tissue expression patterns, and responses to cold and salt stresses, as well as the interactions between OsMORF proteins.…”
Section: Discussionmentioning
confidence: 99%
“…RNA editing is relatively conserved among flowering plants, with types of base conversion including A-to-I, U-to-C, and C-to-U [2]. Among these conversions, the predominant form in plastids and the mitochondria is C-to-U [2,3]. Previous studies showed that there are 30–40 and 400–500 C-to-U conserved RNA editing sites in chloroplasts and mitochondria, respectively, in flowering plants [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations